2021
DOI: 10.1007/s12274-021-3646-y
|View full text |Cite
|
Sign up to set email alerts
|

A stable biocompatible porous coordination cage promotes in vivo liver tumor inhibition

Abstract: Many emerging strategies in chemo-, gene-, and immunotherapy require the accumulation of reagents in the cell nucleus. However, their delivery into the nucleus is often limited. Nuclear delivery could be enhanced with a rationally designed cargo-delivery scaffold, but this approach has rarely been successfully implemented. Herein, a stable, biocompatible molecular capsule that encapsulates and delivers camptothecin, a DNA topoisomerase I inhibitor, into the nucleus of living cells was reported. Nuclear deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…PCC‐6‐M (M=Zn, Co, Ni) was synthesized by a solvothermal approach (Section S3, Supporting Information). PCC‐6‐Zn was formed by the reaction of the vertex ligand (H 4 TBSC, p ‐ tert ‐butylsulfonylcalix[4]arene) and panel ligand (H 3 L, PTH‐COOH) with ZnCl 2 at 130 °C in N,N‐dimethylformamide (DMF) for 48 h. PCC‐6‐Co was obtained with the same procedure as PCC‐6‐Zn with CoCl 2 instead of ZnCl 2 [22] . PCC‐6‐Ni was prepared by using nickel perchlorate as the nickel source, and the reaction time was reduced to 24 h while the amount of DMF was increased.…”
Section: Resultsmentioning
confidence: 99%
“…PCC‐6‐M (M=Zn, Co, Ni) was synthesized by a solvothermal approach (Section S3, Supporting Information). PCC‐6‐Zn was formed by the reaction of the vertex ligand (H 4 TBSC, p ‐ tert ‐butylsulfonylcalix[4]arene) and panel ligand (H 3 L, PTH‐COOH) with ZnCl 2 at 130 °C in N,N‐dimethylformamide (DMF) for 48 h. PCC‐6‐Co was obtained with the same procedure as PCC‐6‐Zn with CoCl 2 instead of ZnCl 2 [22] . PCC‐6‐Ni was prepared by using nickel perchlorate as the nickel source, and the reaction time was reduced to 24 h while the amount of DMF was increased.…”
Section: Resultsmentioning
confidence: 99%
“…40). 195 It was found that CA-PCC 35 is capable of transporting to the cell nucleus and achieving targeted delivery of anti-cancer drugs, dramatically improving the anti-cancer efficacy in vitro . Then, when a liver-cancer-tumor grafted mouse model was used for in vivo study, the drug complex CPT@35 could inhibit tumor growth without damaging other healthy organs in the living mouse.…”
Section: Macrocycle-derived Pccsmentioning
confidence: 99%
“…Herein, we present the recent advances in metal-organic frameworks (MOFs) [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ], covalent organic frameworks (COFs) [ 44 , 45 , 46 , 47 , 48 , 49 ], and porous coordination cages (PCCs) [ 50 , 51 , 52 ] for cancer therapy, mainly in bioimaging, and treatments using photothermal therapy, thermodynamic therapy, or a combination of different therapies in cancer therapy ( Scheme 1 ). We highlight the applications of porous framework materials for bioimaging and cancer therapy in this article ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%